Camundongos tratados com L-Dopa durante o estresse de separação maternal apresentam alterações comportamentais dimórficas - Ana Luiza de Araujo Lima Reis (2017)
It is well known that early life stress can lead to behavioral alterations that might be involved in many neuropsychiatric disorders, including anxiety and depression. Several of these aetiologies emerge during adolescence, when remodeling of the brain occurs. This is one of the reasons that child/adolescent psychiatry practice is still a challenge. Because of this, we investigated the effects of maternal separation (SM) in prepubertal mice behavior. Several studies showed that chronic stress imbalances dopaminergic system. One of the main alterations is a decrease in dopaminergic neurons activity and alterations in dopaminergic receptors expression. So, we investigated if L-Dopa administration during SM can protect against early life stress. Finally, one of the challenges in psychiatry studies is the sex bias in the prevalence of some mental disorders. To tackle this question, we used both males and females C57/BL6 mice. We divided the mice in six experimental groups: non-manipulated group (Naïve) and five groups drug treated and/or submitted to SM protocol (180 min/day) from P2-P14. These groups are: treated with Saline (SAL); L-dopa/Benserazide treated group (50/25 mg / kg) (DOPA); SM group; SM daily treated with Saline (SM+SAL); and L-dopa/Benserazide treated during SM (SM+DOPA). At the 4 week old, their behavior were tested by object recognition task, open field test, elevated plus maze, marble burying and forced swimming test. In addition to the behavioral tests, the animals were submitted to structural magnetic resonance, to analyze the volume of the hippocampus. We have seen that treatment with L-Dopa decreased the depressive like behavior in females and the anxious like behavior in males. When L-Dopa treatment is done along with maternal separation stress, both females and males have an increase in anxious like behavior, but males also show an increase in depressive like behavior. In addition, brain imaging showed a tendency to the decrease of hippocampal volume in SM+DOPA males. Our results suggest a sexual dimorphism in response to treatment with L-Dopa during the maternal separation protocol.